Investigation of vitrification and phase transitions in dough semi-finished products with plant additives - Одарченко, Андрій Миколайович; Сергиенко, Алина Александровна (Eastern-European Journal of Enterprise Technologies, 2015)
The aim of the paper was to investigate the processes of phase transitions and vitrification of water in dough semi-finished product with the plant additive during the freezing and heating, as well as to study the physical state of water at temperatures below 0 °C. Fresh and pre-frozen dough half-finished products were used as the subject of the research. The study of phase transitions and vitrification was performed on a differential scanning calorimeter, designed and manufactured in the IPC&C of the NAS of Ukraine. As a result of the studies, it was determined that the effect of additives on the water state and nature of phase transitions in the water component in the dough at a temperature below 0 °C is caused by the additional content of sugars, proteins and starch, introduced with additives. The state of water in the dough semi-finished products was investigated by nuclear magnetic resonance, during which the spin-spin relaxation time of the samples was determined. It was also found that the pre-freezing increases the water mobility in the samples and introducing additives that contain extra solids by the type of colloids - reduce the water mobility, which in turn provides a better integrity of dough semi-finished products during cold storage.